A Review of Different Techniques Utilized for Crop Yield Prediction - Dayal, Rabina; Yadav, Arun Kumar (International Journal of Computer Sciences and Engineering, 2018)
In India, farmers are not getting expected crop yield from their productions. Crop production mostly depends on weather conditions and some statistical methodologies. To get higher crop production yield, farmers sometimes need advices for predicting and analyzing future crop production. This helps farmers to produce a crop with maximum yield. Such methods will be helpful for farmers and government to make a better decision to increase crop production. In this paper present a review on crop yield prediction (CYP) with different data mining (DM) techniques used to evaluate and predict the problem lead to increase CYP. The result analysis is performed on root mean square error (RMSE) and peak signal noise ratio (PSNR).